Clays and Clay Minerals, Vol. 55, No. 5, 519–523, 2007. - Dolinar, Bojana; Misˇicˇ, Miha; Trauner, Ludvik (The Clay Minerals Society, 2007)
As the water content is increased, the consistency of a fine-grained soil changes from a semisolid state to a plastic stateand finally to a liquid state. Thepl astic limit (PL) is thepoint at which the consistency, caused by the soil water content, is transformed from a semi-solid state to a plastic state. The liquid limit (LL) is the point at which the consistency is transformed from a plastic state to a liquid state. The plastic limit and liquid limit are often collectively referred to as the Atterberg (or consistency) Limits. Although the liquid and plastic limits are easily determined, fundamental interpretations of the limits and quantitative relationships between their values and compositional factors are more complex. Previous studies examined artificially-prepared soil samples that contained monomineralic clays and a non-clay substance(quartz sand). Thesestudie s have shown that in soils without expandableclays thePL and LL water contents were mostly related to surface area and clay content. For soils that contain expandable clays, the PL and LL values are also dependent on interlayer water content. Hence, expandable clay mineral contents are needed to calculate PL and LL values. These relationships have been presented in a general analytical form. The aim of these investigations was to identify practical applications. Mineral compositions and surface areas of five randomly selected natural soil samples were used to estimate PL and LL values. The estimated values were compared to experimentally measured liquid limits (by the ‘fallcone’ test) and plastic limit (by the ‘rolling thread’ test) values. The measured PL values ranged from 18.77 to 44.92% and the LL values from 31.19 to 82.10%. The differences between estimated and measured Atterberg Limits were 3.0-7.1% for thePL and 2.7-7.8% for the LL. Minor differences in measured and estimated Atterberg Limits were probably due to soil organic matter (1.2-2.7%).
Correlation Between Surface Area And Atterberg Limits Of Fine-grained Soils
Clays and Clay Minerals, Vol. 55, No. 5, 519–523, 2007. Correlation Between Surface Area And Atterberg Limits Of Fine-grained Soils. Bojana Dolinar; Miha Misˇicˇ; Ludvik Trauner. DOI: 10.1346/CCMN.2007.0550506. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology